The relationship between the clinical features of idiopathic burning mouth syndrome and self-perceived quality of life - Braud, Adeline; Boucher, Yves (Journal of Oral Science, 2016)
In this descriptive study, we investigated the relationship between the clinical characteristics of idiopathic burning mouth syndrome (iBMS) and the quality of life. Eighteen iBMS patients were interviewed about their experience with pain, oral-associated complaints, cognitive status, and self-perceived quality of life using the French versions of the Hospital Anxiety and Depression Scale (HADS) and the Global Oral Health Assessment Index (GOHAI). The Spearman coefficient was used to analyze correlations. The level of significance was fixed at P < 0.05. The majority of patients described the association of oral burning sensations with other oral complaints, including dry mouth (77.8%), tactile abnormalities (66.7%), thermal abnormalities (44.5%), and taste disturbances (38.9%). HAD-anxiety scores were higher than 10 in 38.8% of iBMS patients and HAD-depression scores were higher than 10 in 33.3% of patients. A significant correlation was found between the number of associated complaints and HAD-depression scores. The mean GOHAI-add score was 37.9 ± 9.6 (mean ± SD), and 94.5% of iBMS patients had a score lower than 50. GOHAI-add scores strongly correlated with pain intensity, which was calculated using a visual analog scale and duration of pain. Our findings indicate a strong correlation between iBMS-related pain and self-perceived oral health-related quality of life. In addition, a correlation was observed between iBMS-associated oral complaints and cognitive status.(J Oral Sci 58, 475-481, 2016)